A new approach for hemodynamics of varicoceles: blood flow patterns based on contrast-enhanced ultrasound - Penglin Zou; Gaoxiang Fan; Zheng Li; Yuchen Tao; Chao Jia; Hongmei Liang; Ruhui Tian; Qiusheng Shi; Jianlin Hu; Rong Wu (Basic and Clinical Andrology)
Abstract Background Hemodynamic alterations in the spermatic vein are implicated in infertility among patients with varicocele (VC). Contrast-enhanced ultrasound (CEUS), a powerful tool for hemodynamic analysis, remains unexplored for VC. This study aimed to demonstrate the feasibility of using CEUS to evaluate spermatic vein hemodynamics in patients with VC and establish a clear correlation between specific hemodynamic patterns and impaired semen parameters. This study included 165 patients with left-sided VC and 50 healthy volunteers. All participants underwent CEUS of the spermatic veins, along with maximum venous diameter and testicular volume measurements and serum sex hormone levels and routine semen analyses. The sperm DNA fragmentation index was measured in 146 patients with VC and 37 healthy controls. Results The analyses revealed four distinct blood flow patterns of the spermatic vein: steady flow, intermittent stasis, intermittent reflux, and filling defect. In healthy spermatic veins, the predominant blood flow patterns included steady flow and intermittent stasis. Spermatic veins with VC exhibited a significant increase in the intermittent reflux and filling defect patterns, with the proportion rising as the clinical grade increased. The four patterns were further grouped into the “steady flow & intermittent stasis” and “intermittent reflux & filling defect” patterns for logistic regression analyses; the intermittent reflux & filling defect pattern was revealed as an independent risk factor for impaired sperm concentration, total sperm counts, progressive motility, morphology, and DNA fragmentation index. Conclusions This study validated the feasibility of CEUS for assessing the hemodynamics of the spermatic vein and established the intermittent reflux & filling defect pattern as an independent predictor of impaired semen parameters.